Optimalisasi Pertumbuhan Dan Perkembangan Anak Usia Dini Dengan Bina Keluarga Balita Holistik Integratif - Fahmaningtyas, Rismala Putri (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2020)
Growth and development toddler can be important for future. Toddler’s period is a golden age because at the moment, their brains are 80 percent developed. Toddler needs stimulations and support from their families so that they can growth and development optimally. Bina Keluarga Balita is place for family who have a toddler where they can discuss and exchange ideas or information about growth and development toddler. Parents who follow Bina Keluarga Balita can see their child’s development with milestone’s card and the can get many sklills of parenting. The result of this research is encourage parent’s stimulate their children according to the stage of growth and development optimally